Evaluation of Yazd Dental Intern's Awareness and Refer Percentage about Endodontic Accidents in 2020-2021 - Mehdi Tabrizizadeh; Zahra Asheghmoalla; Maryam Kazemipoor (Mashhad University of Medical Sciences, 2022)
Introduction: During root canal treatment, unpredictable conditions might occur that awareness of their prevention, diagnosis, and treatment is highly effective in the long-term prognosis of the teeth. The purpose of the present study was to evaluate the awareness of Yazd dental interns about endodontic accidents in 2020-2021.Materials and Methods: The participants of this descriptive cross-sectional study included 59 dental interns. The instrument used in this study was a researcher-made questionnaire. The validity and reliability of the designed questionnaire were approved through three stages. For the qualitative recording of the students' knowledge, the scores were categorized as weak, moderate, and fair. Data were analyzed in SPSS software version 17 using a t-test and Pearson correlation coefficient. The significance level in this study was 0.05.Results: In this study, out of 59 students, 25 (42.4%) and 34 (57.6%) were male and female, respectively. The total mean score of students' awareness was 14.05±1.07 with a minimum of 7 and a maximum of 20. The average total awareness score was assessed as moderate. There was a positive correlation between students' awareness score and their GPA (r=0.386, P=0.001). There was no significant difference between male and female students' awareness scores (P=0.246). According to students' scores in the four fields, the highest mean score was related to cleansing and shaping while the lowest average was related to post space preparation and vertical root fracture.Conclusion: Based on the results of the present study, the dental students' awareness of endodontic accidents was at a moderate level. It is recommended that educational interventions and appropriate strategies be adopted to promote students' knowledge.